High-strength and high-temperature-resistant titanium-copper alloy and preparation method thereof

Through high -energy ball grinding and advanced sintering technology, titanium copper alloys are prepared, and multiple cold rolling and solid solution treatment are performed, which solves the problem of instability of titanium copper alloy in high temperature environments, and realizes high -strength and high temperature resistance. Titanium copper alloy meets the high performance needs of electronic components.

CN119372518APending Publication Date: 2025-01-28NINGXIA CNMC NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411576795.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The existing titanium copper alloys have unstable performance in high temperature environments, making it difficult to meet the demands of electronic components for high strength, high temperature resistance and low energy consumption.

Method used

Prepare composite powder through high -energy ball grinding grinding, use heat such as heat -static sintering or discharged plasma sintering technology to prepare titanium copper alloy ingots, and perform multiple cold rolled, solid -soluble and high -temperature short -term continuous timeliness to form a stable nanometer precipitation Phase and uniform grain structure.

Benefits of technology

It significantly improves the strength and temperature resistance of titanium alloy, meets the demand for high performance of electronic components, and provides new process paths to meet market demand and technological development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005121987160000031
    Figure BDA0005121987160000031
  • Figure BDA0005121987160000071
    Figure BDA0005121987160000071
  • Figure FDA0005121987130000021
    Figure FDA0005121987130000021
Patent Text Reader

Abstract

The invention provides a high-strength and high-temperature-resistant titanium-copper alloy and a preparation method thereof, and belongs to the technical field of alloy material treatment.The preparation method comprises the steps that titanium powder, nickel powder, iron powder, cobalt powder, copper powder and rare earth element X powder are placed in a ball milling tank, then air in the ball milling tank is replaced with argon, high-energy ball milling is conducted after hard alloy grinding balls are added, and the alloy powder is obtained; composite powder is obtained; the composite powder is put into a graphite mold, sintering and homogenization are conducted in sequence, and a titanium-copper alloy cast ingot is obtained; the method comprises the following steps: sequentially carrying out primary large-machining-rate cold rolling and cleaning on a titanium-copper alloy ingot, carrying out solution treatment under the protection of inert gas, sequentially carrying out secondary large-machining-rate cold rolling and cleaning, and finally carrying out continuous high-temperature short-time continuous aging in a continuous reducing atmosphere. The strength performance and the temperature resistance of the titanium-copper alloy can meet the performance requirements of electronic components, and technical innovation and product upgrading in the electronic component industry can be achieved easily.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of alloy material processing, and in particular relates to a high-strength and high-temperature-resistant titanium-copper alloy and a preparation method thereof. Background Art

[0002] High-strength and high-conductivity copper alloys are widely used in various high-tech fields due to their excellent performance, such as integrated circuit lead frames, high-speed railway contact network cables, and nuclear fusion heat dissipation materials. However, with the rapid development of the aerospace field, more stringent requirements have been placed on the performance of copper alloys, which not only need to have good electrical and thermal conductivity, but also excellent high temperature resistance.

[0003] Copper-beryllium alloy is called "the king of the king of non-ferrous elastic materials". After proper aging heat treatment, its tensile strength is 1000MPa and its conductivity is 20%IACS. It is widely used in elastic components, relay springs, bearings, special five-spark tools, etc. However, the production and application of beryllium are limited by the following factors: small domestic raw material reserves, high production costs of enterprises, dust generated by processing is toxic to humans and the environment, high processing conditions are required, and it is not suitable for use above 200℃.

[0004] Titanium copper alloy has ultra-high strength, high elastic modulus, high bending performance and high stress relaxation performance. As an ultra-high strength conductive material, titanium copper alloy has replaced traditional Cu-Be alloy in applications such as conductive springs and interconnectors. However, innovations in fields such as nanotechnology, new materials and new energy have put forward higher requirements for copper alloys used in components. Consumers' pursuit of portability, comfort and aesthetics has prompted manufacturers to continuously reduce product size and improve performance. The expansion of application areas, such as 5G, Internet of Things, smart terminals and automotive electronics, has led to an increasing demand for miniaturized and high-performance components. In order to achieve smaller size, higher performance and lower energy consumption, higher requirements are placed on the performance of titanium copper alloys. It is urgent to develop high-strength and high-temperature-resistant titanium copper alloys from the aspects of green and environmentally friendly preparation process, precise chemical composition, low impurity content and high thermal stability to achieve technological innovation and product upgrades in the electronic components industry to adapt to the ever-changing market demand and technological development. Summary of the invention

[0005] One of the purposes of the present invention is to provide a method for preparing a high-strength and high-temperature-resistant titanium-copper alloy. The strength and temperature resistance of the titanium-copper alloy prepared by this method can meet the performance requirements of electronic components, which is conducive to realizing technological innovation and product upgrading in the electronic components industry.

[0006] A second object of the present invention is to provide a titanium-copper alloy with high strength and high temperature resistance.

[0007] In order to achieve one of the above purposes, the present invention adopts the following technical solution:

[0008] A method for preparing a high-strength and high-temperature-resistant titanium-copper alloy, the preparation method comprising:

[0009] Step S1, according to the components and mass percentages of the titanium-copper alloy, titanium powder, nickel powder, iron powder, cobalt powder, copper powder and rare earth element X powder are placed in a ball mill, and then the air in the ball mill is replaced with argon gas, and hard alloy grinding balls are added to perform high-energy ball milling to obtain a composite powder;

[0010] Step S2, loading the composite powder into a graphite mold, then placing a layer of carbon paper on both inner sides of the composite powder and the graphite mold, placing a round carbon paper between the composite powder and the upper pressure head and between the composite powder and the lower pressure head, and then sintering, heating and homogenizing in sequence to obtain a titanium-copper alloy ingot;

[0011] Step S3, the titanium-copper alloy ingot is sequentially subjected to a high-processing rate cold rolling and cleaning, then subjected to a solid solution treatment under the protection of an inert gas, then subjected to a second high-processing rate cold rolling and cleaning, and finally subjected to continuous high-temperature short-time continuous aging in a continuous reducing atmosphere.

[0012] Furthermore, in step S1, the components and mass percentages of the titanium-copper alloy are:

[0013] Ti, 2-3.5wt%; Ni≤0.1%; Co≤0.1%; Fe≤0.15%; X≤0.05%, the balance is copper;

[0014] The rare earth element X is one of Ce, La, Sc and Y or a mixture of two or more thereof.

[0015] Furthermore, in the step S1, the purity of the titanium powder, nickel powder, iron powder, cobalt powder, copper powder and rare earth element X powder is greater than or equal to 99%, the mesh size is 190-200 mesh, and the particle size is ≤30 μm.

[0016] Furthermore, in the step S1, the ball-to-material ratio in the high-energy ball milling is 4 to 6:1, the ball milling speed is 50 to 500 rpm / min, and the ball milling time is 15 to 20 hours;

[0017] The hard alloy grinding ball is one of stainless steel, zirconium oxide and bearing steel, and the size of the grinding ball is 2-5 mm.

[0018] Furthermore, in the step S2, the sintering is hot isostatic pressing sintering or spark plasma sintering;

[0019] In step S2, the process conditions of hot isostatic pressing sintering are: temperature of 770°C to 870°C, pressure of 147 to 153 MPa, holding time of 1.6 to 2.4 hours and then cooling to room temperature;

[0020] In step S2, the sintering is spark plasma sintering; the specific process of the spark plasma sintering is: the graphite mold is pre-pressed and placed in a spark plasma sintering device, and then heated to 570-630° C. under a vacuum state, kept warm for 3-7 minutes and then exhausted; then heated to 870-930° C. under a pressure of 30-50 MPa, kept warm for 5-15 minutes and then cooled to room temperature.

[0021] Furthermore, in step S2, the homogenization temperature is 760-900° C., and the holding time is:

[0022]

[0023] Among them, T is the holding time (i.e., homogenization time); h is the thickness of the titanium-copper alloy ingot; v is the thermal conductivity, which is 35 to 45 mm / min; and t is the preset time range, which is 70 to 80 min.

[0024] Furthermore, in the step S3, the total processing rates of the first high processing rate cold rolling and the second high processing rate cold rolling are both greater than 90%.

[0025] Furthermore, in step S3, the process conditions of the solution treatment are: the cooling method is solid CO2 cooling, the solution treatment temperature is 760-910°C, and the solution treatment time is 60-900s;

[0026] In the step S3, the temperature of the continuous high-temperature short-time continuous aging is 480-570°C, the speed is 12-24 m / min, and the time is 80-90 s.

[0027] In order to achieve the second objective above, the present invention adopts the following technical solution:

[0028] A high-strength and high-temperature-resistant titanium-copper alloy is prepared by the above-mentioned preparation method.

[0029] In summary, the technical solution of the present invention has the following technical effects:

[0030] The invention prepares a composite powder of 15 to 33 μm rare earth and trace element alloying by high-energy ball milling mechanical alloying of copper powder, titanium powder and rare earth elements. The composite powder is subjected to hot isostatic pressing sintering or spark plasma sintering to prepare a titanium-copper alloy ingot with uniform and fine grains and sufficient alloying, thereby avoiding the problem of copper slag mixing in vacuum smelting or non-vacuum smelting, which easily causes slag curling and re-polluting the titanium-copper alloy ingot. The titanium-copper alloy ingot is sequentially subjected to a high-processing rate cold rolling, cleaning, solid solution, a secondary high-processing rate cold rolling and cleaning to form a dispersed nano-precipitated phase, which effectively pins grain boundaries and dislocations, inhibits grain growth and provides a higher strengthening effect, so that Titanium-copper alloy has extremely excellent organizational stability and mechanical properties (high strength and high temperature resistance); the present invention adopts a continuous high-temperature short-time continuous aging method under a continuous reducing atmosphere to achieve a significant reduction in the grain size deviation of the titanium-copper alloy strip foil to 2-3μm / 100m, thereby obtaining a titanium-copper alloy with double uniform characteristics, whose strength and temperature resistance meet the performance requirements of electronic components, realizes technological innovation and product upgrades in the electronic components industry, and can adapt to the ever-changing market demands and technological developments. This innovative method not only improves the performance of the material, but also provides a new process path for the processing and application of titanium-copper alloys. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention is clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] This embodiment provides a method for preparing a high-strength and high-temperature-resistant titanium-copper alloy. The preparation method comprises:

[0033] Step S1, according to the components and mass percentages of the titanium-copper alloy, titanium powder, nickel powder, iron powder, cobalt powder, copper powder and rare earth element X powder are placed in a ball mill, the air in the ball mill is replaced with argon, and hard alloy grinding balls are added to perform high-energy ball milling to obtain a composite powder.

[0034] Based on the traditional titanium-copper alloy, this embodiment redesigns the Ti content and the content of the main alloying elements Ni, Co, and Fe to improve the electrical conductivity, strength, and thermal stability of the alloy from the perspective of composition. By controlling the ratio of the Ti element to Ni, Co, and Fe, it is ensured that the alloy matrix has a suitable proportion of alloying elements, and after subsequent solid solution and aging strengthening treatment, a stable, finely dispersed second phase is formed to improve the strength of the alloy.

[0035] In order to ensure the size and distribution of the precipitated phase in the alloy, the addition amount of Ni and Fe must be specified. The addition amount of Ni and Fe should satisfy C=0~0.25 (Ni+Fe), preferably 0.01~0.02 (Ni+Fe). Under this condition, the stable and controllable precipitation of Ni and Fe can be guaranteed, and the titanium-copper alloy can maintain a certain toughness while ensuring high strength, and stabilize the thermal stability coefficient of the alloy. The role and proportion of the above elements are introduced as follows:

[0036] Ti: Titanium is an essential element for the precipitation phase in the alloy, and together with other precipitation phase elements, it determines the type, size and distribution state of the precipitation phase. Therefore, a certain lower limit of titanium must be guaranteed to ensure the precipitation of the alloy; at the same time, too much titanium will cause the carbide precipitation phase to be too large, deteriorating the strength, toughness and thermal stability of the alloy. The titanium content of the present invention is designed to be 2-3.5%, preferably 2.5-3.0%.

[0037] Ni: Ni is an essential element to ensure that the alloy has heat resistance. In the present invention, since Ni3Ti is formed with titanium during the aging process, the heat resistance and strength of the alloy will be improved to a certain extent. Therefore, the content of Ni must be properly controlled. The present invention stipulates that the Ni content is ≤0.1%, preferably 0.075-0.085%.

[0038] Fe: Fe can refine grains, increase plasticity, and inhibit grain boundary reactions during aging. Through the processing technology of the present invention, fine dispersed precipitates such as ferrous intermetallic compounds can be formed to improve the strength of the alloy. However, the addition of Fe will increase the brittleness of the alloy and affect its formability, and its upper limit is set to 0.15%, preferably 0.10-0.13%.

[0039] Cerium (Ce): Cerium is a strong deoxidizer that can reduce the oxygen content in copper alloys, thereby improving the plasticity and toughness of the alloy. Cerium can also refine the grains and improve the strength and corrosion resistance of the alloy.

[0040] Lanthanum (La): Lanthanum can be used as a grain refiner to improve the microstructure of the alloy and enhance the mechanical properties of the material. Lanthanum can also improve the oxidation resistance and corrosion resistance of copper alloys.

[0041] Scandium (Sc): Scandium is an effective grain refiner that can significantly improve the strength and toughness of copper alloys. Scandium can also improve the electrical conductivity and corrosion resistance of copper alloys.

[0042] Yttrium (Y): Yttrium can improve the high temperature strength and oxidation resistance of copper alloys, making them suitable for high temperature applications. Yttrium can also improve the processing and welding properties of alloys.

[0043] In summary, the components and mass percentages of the titanium-copper alloy in this embodiment are:

[0044] Ti, 2-3.5wt%; Ni≤0.1%; Co≤0.1%; Fe≤0.15%; X≤0.05%, and the balance is copper.

[0045] The purity of the titanium powder, nickel powder, iron powder, cobalt powder, copper powder and rare earth element X powder in this embodiment is greater than or equal to 99%, the mesh size is 190-200 mesh, and the particle size is ≤30 μm, preferably 20-25 μm. The rare earth element X is one or a mixture of two or more of Ce, La, Sc and Y. The mass percentage of Co is preferably 0.08-0.09%, and the mass percentage of X is preferably 0.02-0.04%.

[0046] In this embodiment, after 3-4 times of vacuuming and filling with argon, the air in the ball mill is replaced with argon to prevent oxidation of the powder during the ball milling process. The ball-to-material ratio in the high-energy ball mill in this embodiment is 4-6:1, the ball milling speed is 50-500rpm / min, and the ball milling time is 15-20 hours. The cemented carbide grinding ball is one of stainless steel, zirconium oxide, and bearing steel, and the grinding ball particle size is 2-5mm.

[0047] Step S2, loading the composite powder into a graphite mold, then placing a layer of carbon paper on both inner sides of the composite powder and the graphite mold, placing round carbon paper between the composite powder and the upper pressure head and between the composite powder and the lower pressure head, and then sintering, heating and homogenizing are performed in sequence to obtain a titanium-copper alloy ingot.

[0048] A layer of carbon paper is wrapped between the powder (composite powder) and the mold (graphite mold), and two round pieces of carbon paper are placed between the powder (composite powder) and the upper and lower pressure heads to prevent adhesion.

[0049] The sintering in this embodiment is hot isostatic pressing sintering or spark plasma sintering, wherein the process conditions of hot isostatic pressing sintering are: temperature of 770° C. to 870° C., pressure of 147 to 153 MPa, and holding time of 1.6 to 2.4 h.

[0050] The specific process of spark plasma sintering is as follows: the graphite mold is pre-pressed and placed in the spark plasma sintering equipment, and then heated to 570-630°C under a vacuum state, kept warm for 3-7 minutes and then exhausted; then heated to 870-930°C under a pressure of 30-50MPa, kept warm for 5-15 minutes, and finally a uniform phase is obtained. After the insulation is completed, the temperature is lowered to room temperature to obtain a titanium-copper alloy material.

[0051] The homogenization temperature in this embodiment is 760-900°C, and the heating time is longer than the homogenization time determined by the dendrite spacing and diffusion coefficient, and the heating time is generally 3-4 hours. It is usually longer than the holding time, and the holding time is;

[0052]

[0053] Among them, T is the holding time; h is the thickness of the titanium-copper alloy ingot; v is the thermal conductivity, which is 35 to 45 mm / min; and t is the preset time range, which is 70 to 80 min.

[0054] Step S3, the titanium-copper alloy ingot is sequentially subjected to a high-processing rate cold rolling and cleaning, then subjected to a solid solution treatment under the protection of an inert gas, then subjected to a second high-processing rate cold rolling and cleaning, and finally subjected to continuous high-temperature short-time continuous aging in a continuous reducing atmosphere.

[0055] The first high processing rate cold rolling and the second high processing rate cold rolling in this embodiment are multi-pass (3-4 passes) finishing rolling with a total processing rate greater than 90%, and are cleaned after rolling to the finished product size, and the grain size of the strip foil reaches 15-25μm. The total processing rate is preferably 92-94%.

[0056] The process conditions of the solution treatment are: the cooling method is solid CO2 cooling, the solution treatment temperature is 760-910°C, and the solution treatment time is 60-900s.

[0057] The temperature of continuous high temperature short-time continuous aging is 480-570°C, the speed is 12-24m / min, and the time is 80-90s.

[0058] The technical solution is introduced with specific embodiments below:

[0059] Embodiment 1:

[0060] Step S1, according to the various components and mass percentages of the titanium-copper alloy, titanium powder, nickel powder, iron powder, cobalt powder, copper powder and Ce powder are placed in a ball mill, and then the air in the ball mill is replaced with argon gas, and stainless steel with a size of 2 mm is added, and high-energy ball milling is performed for 20 hours at a ball mill speed of 50 rpm / min to obtain a composite powder.

[0061] The components and mass percentages of the titanium-copper alloy are: Ti, 2.0%; Ni, 0.1%; Co, 0.1%; Fe, 0.15%; Ce, 0.05%, and the balance is copper. The purity of titanium powder, nickel powder, iron powder, cobalt powder, copper powder and Ce powder is 99%, the mesh number is 195 mesh, and the particle size is 20μm. The ball-to-material ratio in the high-energy ball mill is 5:1.

[0062] Step S2, loading the composite powder into a graphite mold, and then placing a layer of carbon paper on both inner sides of the composite powder and the graphite mold, placing round carbon paper between the composite powder and the upper pressure head and between the composite powder and the lower pressure head, hot isostatically pressed and sintered at a temperature of 870°C and a pressure of 147MPa for 2h, cooled to room temperature, and then heated to 760°C and homogenized for 3.5h to obtain a titanium-copper alloy ingot.

[0063] Step S3, the titanium-copper alloy ingot is sequentially subjected to a high-processing rate cold rolling and cleaning, then subjected to a solid solution treatment under the protection of an inert gas, then subjected to a second high-processing rate cold rolling and cleaning, and finally subjected to continuous high-temperature short-time continuous aging in a continuous reducing atmosphere.

[0064] The first high processing rate cold rolling and the second high processing rate cold rolling in this embodiment are both three-pass finishing rolling with a total processing rate of 92%. After rolling to the finished product size, cleaning is carried out, and the grain size of the strip foil reaches 15μm.

[0065] The process conditions of the solution treatment are: the cooling method is solid CO2 cooling, the solution treatment temperature is 760°C, and the solution treatment time is 60s.

[0066] The temperature of continuous high temperature short time continuous aging is 570℃, the speed is 24m / min, and the time is 80s.

[0067] The tensile strength of the titanium-copper alloy of this embodiment is 1160 MPa, and the high temperature resistance performance reaches a stress relaxation rate of 5.6% at 120° C. for 1000 h.

[0068] Embodiment 2:

[0069] Step S1, according to the various components and mass percentages of the titanium-copper alloy, titanium powder, nickel powder, iron powder, cobalt powder, copper powder and La+Y powder are placed in a ball mill, and then the air in the ball mill is replaced with argon gas, and zirconium oxide with a size of 5 mm is added, and high-energy ball milling is performed for 15 hours at a ball mill speed of 500 rpm / min to obtain a composite powder.

[0070] The components and mass percentages of the titanium-copper alloy are: Ti, 3.5%; Ni, 0.085%; Co, 0.09%; Fe, 0.13%; La+Y, 0.04%, and the balance is copper. The purity of titanium powder, nickel powder, iron powder, cobalt powder, copper powder and La+Y powder is 99.5%, the mesh number is 190 mesh, and the particle size is 30μm. The ball-to-material ratio in the high-energy ball mill is 4:1.

[0071] Step S2, loading the composite powder into a graphite mold, then placing a layer of carbon paper on both inner sides of the composite powder and the graphite mold, placing round carbon paper between the composite powder and the upper pressure head and between the composite powder and the lower pressure head, hot isostatically pressing and sintering for 2.4 hours at a temperature of 770°C and a pressure of 153MPa, cooling to room temperature, then heating to 900°C, and homogenizing for 3 hours to obtain a titanium-copper alloy ingot.

[0072] Step S3, the titanium-copper alloy ingot is sequentially subjected to a high-processing rate cold rolling and cleaning, then subjected to a solid solution treatment under the protection of an inert gas, then subjected to a second high-processing rate cold rolling and cleaning, and finally subjected to continuous high-temperature short-time continuous aging in a continuous reducing atmosphere.

[0073] The first high processing rate cold rolling and the second high processing rate cold rolling in this embodiment are both 4-pass finishing rolling with a total processing rate of 90%. After rolling to the finished product size, cleaning is performed, and the grain size of the strip foil reaches 25μm.

[0074] The process conditions of the solution treatment are: the cooling method is solid CO2 cooling, the solution treatment temperature is 910°C, and the solution treatment time is 900s.

[0075] The temperature of continuous high temperature short time continuous aging is 480℃, the speed is 12m / min, and the time is 90s.

[0076] The tensile strength of the titanium-copper alloy of this embodiment is 1130 MPa, and the high temperature resistance performance reaches a stress relaxation rate of 5.2% at 120° C. for 1000 h.

[0077] Embodiment 3:

[0078] This embodiment is basically the same as Embodiment 1, except that:

[0079] The ball-to-material ratio in high-energy ball milling is 6:1.

[0080] The sintering is spark plasma sintering. The specific process of spark plasma sintering is: the graphite mold is pre-pressed and placed in the spark plasma sintering equipment, and then heated to 630°C under vacuum, kept warm for 7 minutes and then exhausted; then heated to 930°C under a pressure of 30MPa, kept warm for 15 minutes and then cooled to room temperature.

[0081] The tensile strength of the titanium-copper alloy of this embodiment is 1180 MPa, and the high temperature resistance performance reaches a stress relaxation rate of 6.0% at 120° C. for 1000 h.

[0082] Embodiment 4:

[0083] This embodiment is basically the same as Embodiment 2, except that:

[0084] The sintering is spark plasma sintering. The specific process of spark plasma sintering is: the graphite mold is pre-pressed and placed in the spark plasma sintering equipment, and then heated to 570°C under vacuum, kept warm for 3 minutes and then exhausted; then heated to 870°C under a pressure of 50MPa, kept warm for 5 minutes and then cooled to room temperature.

[0085] The tensile strength of the titanium-copper alloy of this embodiment is 1150 MPa, and the high temperature resistance performance is that the stress relaxation rate reaches 5.0% at 120° C. for 1000 h.

[0086] Please note that the technical features of the above embodiments can be combined arbitrarily. In order to make the description concise, all possible combinations of the technical features in the above embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. The above embodiments only express several implementation methods of the present application, and their descriptions are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present application, several variations and improvements can be made, which all belong to the scope of protection of the present application. Therefore, the scope of protection of the patent in this application shall be based on the attached claims.

Claims

1. A method for preparing a high-strength and high-temperature-resistant titanium-copper alloy, characterized in that: The preparation method comprises: Step S1, according to the components and mass percentages of the titanium-copper alloy, titanium powder, nickel powder, iron powder, cobalt powder, copper powder and rare earth element X powder are placed in a ball mill, and then the air in the ball mill is replaced with argon gas, and hard alloy grinding balls are added to perform high-energy ball milling to obtain a composite powder; Step S2, loading the composite powder into a graphite mold, then placing a layer of carbon paper on both inner sides of the composite powder and the graphite mold, placing a round carbon paper between the composite powder and the upper pressure head and between the composite powder and the lower pressure head, and then sintering and homogenizing in sequence to obtain a titanium-copper alloy ingot; Step S3, the titanium-copper alloy ingot is sequentially subjected to a high-processing rate cold rolling and cleaning, then subjected to a solid solution treatment under the protection of an inert gas, then subjected to a second high-processing rate cold rolling and cleaning, and finally subjected to continuous high-temperature short-time continuous aging in a continuous reducing atmosphere.

2. The preparation method according to claim 1, characterized in that: In step S1, the components and mass percentages of the titanium-copper alloy are: Ti, 2-3.5wt%; Ni≤0.1%; Co≤0.1%; Fe≤0.15%; X≤0.05%, the balance is copper; The rare earth element X is one of Ce, La, Sc and Y or a mixture of two or more thereof.

3. The preparation method according to claim 2, characterized in that: In the step S1, the purity of the titanium powder, nickel powder, iron powder, cobalt powder, copper powder and rare earth element X powder is greater than or equal to 99%, the mesh number is 190-200 mesh, and the particle size is ≤30 μm.

4. The preparation method according to any one of claims 1 to 3, characterized in that: In the step S1, the ball-to-material ratio in the high-energy ball mill is 4-6:1, the ball milling speed is 50-500 rpm / min, and the ball milling time is 15-20 hours; The hard alloy grinding ball is one of stainless steel, zirconium oxide and bearing steel, and the size of the grinding ball is 2-5 mm.

5. The preparation method according to claim 4, characterized in that: In the step S2, the sintering is hot isostatic pressing sintering or spark plasma sintering; In step S2, the process conditions of hot isostatic pressing sintering are: temperature of 770°C to 870°C, pressure of 147 to 153 MPa, holding time of 1.6 to 2.4 hours and then cooling to room temperature; In step S2, the sintering is spark plasma sintering; the specific process of the spark plasma sintering is: the graphite mold is pre-pressed and placed in a spark plasma sintering device, and then heated to 570-630° C. under a vacuum state, kept warm for 3-7 minutes and then exhausted; then heated to 870-930° C. under a pressure of 30-50 MPa, kept warm for 5-15 minutes and then cooled to room temperature.

6. The preparation method according to claim 5, characterized in that: In step S2, the homogenization temperature is 760-900° C., and the holding time is: Among them, T is the holding time; h is the thickness of the titanium-copper alloy ingot; v is the thermal conductivity, which is 35 to 45 mm / min; and t is the preset time range, which is 70 to 80 min.

7. The preparation method according to claim 6, characterized in that: In the step S3, the total processing rates of the first high processing rate cold rolling and the second high processing rate cold rolling are both greater than 90%.

8. The preparation method according to claim 7, characterized in that: In step S3, the process conditions of the solution treatment are: the cooling method is solid CO2 cooling, the solution treatment temperature is 760-910°C, and the solution treatment time is 60-900s; In the step S3, the temperature of the continuous high-temperature short-time continuous aging is 480-570°C, the speed is 12-24 m / min, and the time is 80-90 s.

9. A high-strength and high-temperature-resistant titanium-copper alloy, characterized in that: The high-strength and high-temperature-resistant titanium-copper alloy is prepared by the preparation method described in any one of claims 1 to 8.